Ranibizumab for Choroidal Neovascularization Secondary to Choroidal Osteoma Associated and Central Serous Choroidopathy - Dolz-Marco, Rosa; Martínez-Castillo, Sebastián; Shields, Carol L.; Gallego-Pinazo, Roberto; Díaz-Llopis, Manuel (Journal of Ocular Diseases and Therapeutics, 2013)
Purpose: To describe a case of atypical choroidal osteoma with secondary choroidal neovascularization associated with chronic central serous chorioretinopathy. Case Report: A 46-year-old man presented with a 6-month history of vision loss in his left eye (OS). The visual acuity was 20/30 in his OS. Dilated fundus examination OS evidenced a whitish deep lesion in the superior temporal arcade suggestive of choroidal osteoma. Spectral-domain optical coherence tomography revealed a serous macular detachment with a heterogeneous hyperreflective intrachoroidal mass within the superior temporal major arcade with overlying cystoid macular edema, and a temporal macular pigment epithelial detachment. An intravitreal injection of ranibizumab was administered and one month later the visual acuity improved to 20/25 and the subretinal fluid partially regressed. Conclusion: Although choroidal osteoma has no definite therapeutic approach, it may associate secondary complications. Patients should be monitored in order to detect changes suitable for potential therapies available and therefore minimize the visual burden of the disease.